From dividual and individual selves to porous subjects - Smith, Karl (The Australian journal of anthropology, 2012)
The distinction between understanding persons as dividuals versus individuals began to develop in the latter half of the twentieth century. Originating in Louis Dumont’s comparative work into the differences between Western and Indian subjects in the 1950s, it perhaps reached its zenith in the 1980s when Marilyn Strathern used it to differentiate between Melanesian and Western concepts of the person. By the end of the century, critique and reconceptualisation of the individual:dividual distinction was so well established in the anthropological literature that its explanatory capacity was largely negated. The aim of this paper is to attempt to clarify the different modes of personhood that the dividual:individual distinction sought to elucidate by introducing a useful distinction between the self and the human subject and further developing Charles Taylor’s distinction between porous and buffered selves.